View of the small mandapa in front of the maha mandapa - Temples of India Project Team (Jio Institute, 2024)
A small shrine, possibly a newer construction, is placed off-centred to the right facing the garbhagriha. Further steps lead to the third level, on a projected platform. Pieces from the temple have been repurposed in this shrine. Inside view of the small mandapa in front of the mahamandapa. The structure has arched openings on the west, east, and north (seen here) sides with a rectangular entrance inside an arched niche on the south side. A Shiva lingam made in black stone is installed inside with a Nandi figure next to it. An earthen pot is installed on a tripod which drips water over the Shiva lingam.